Iowa Birdline update, November 7, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for November 7, 1988. Highlights of the update include two flybys in central Iowa, one of which, a Yellow Billed Loon, would be a first state record. Also of note were sightings of a Prairie Falcon, White-winged Scoters, Horned Grebes, Hooded Mergansers, Snow Buntings, and Common Loons. Another interesting observation was of an albino Red-winged Blackbird. Epson - sheet feed/flatbed